The Implementation of Non-Refoulement Principle to the Asylum Seekers and Refugees in Indonesia - M. Alvi Syahrin (Faculty of Law, Sriwijaya University, Indonesia, 2017)
The expulsion of refugees, either by the state party or by the non-state party to the 1951 Refugee Convention or countries has protracted the refugees’ suffering. Some countries which are the parties to the 1951 Convention even drive out the refugees to outside their national territory for reasons that the refugees were threatening national security or disturbing public order in the country. In the discussion, it is found that firstly, the principle of non-refoulement is a jus cogen and has become customary international law. The non-refoulement principle has legal binding power to both the State party and the non-State party to the 1951 Refugee Convention. Secondly, according to Article 32 paragraph 1 of the 1951 Convention, the implementation of the principle of non-refouelement is not absolute. Exceptions can only be made if the refugees concerned become a threat to national security and disturb public. Thirdly, Indonesia has not yet the State Party to the Refugee Convention of 1951 but Indonesia is subject to the principle of non-refouelement. This is because (i) Indonesia has ratified the Convention against Torture, the Fourth Geneva Convention Relative to the Protection of Civilian Person in Time of War and the ICCPR/International Covenant on Civil and Political Rights (set on the principle of non-refoulement), (ii) the obligation of the state to rule of customary international law (based on the moral and ethical aspects of the enforcement of international law), and (iii) there is legal instrument issued by the government related to the principle of the principle of non-refouelement; Fourth, there is no written sanctions imposed on Indonesia if violations of international law are with regard to the refugee problems.